GROWING CONDITIONS INFLUENCE ON PHYTOMASS PRODUCTIVITY OF SWITCH-GRASS (PANICUM VIRGATUM L.)OF THE SECOND VEGETATION YEAR - Кулик, М. І. (Scientific Progress & Innovations, 2013)
Peculiarities of forming switch-grass phytomass productivityduring growing on the degraded soils for obtaining raw material for biofuel production are given. Phenologicalobservations such asinterphase perioddurationduring the second year crop vegetation are made. The quantitative indexes of plantvegetative part,correlation of these indexes and influence on crop productivity are established. Switch-grass phytomass productivity of the experimentedvarietieswith different space width between rows is defined.